Структурні особливості та властивості зміцненої алюмооксидної кераміки - Давидчук, Н.К. (Вісник Українського матеріалознавчого товариства, 2013)
The processes of formation of fine composite powder (ligatures) in collaboration nestihiiometrichnogo silicon carbide with titanium oxide were investigated. Creation by hot pressing of high-density alumina ceramic, reinforced synthetic powder ligature. Phase composition, characteristics of structure and mechanical properties of the samples were discussed. We consider the practical use of the developed material as a cutting tool.